Chanling Gao Attenuates Bone Cancer Pain in Rats by the IKKβ/NF-κB Signaling Pathway - Yang, Bing; Zhang, Zhen; Yang, Zhu; Ruan, Jinghua; Luo, Li; Long, Fengxi; Tang, Dongxin (Frontiers in Pharmacology, 2020)
Cancer pain is one of the most common and serious symptoms of cancer patients. At present, the agents used for the prevention or treatment of cancer pain do not act with optimal safety and efficacy. The nuclear factor kappa B (NF-κB) signaling pathway and its downstream inflammatory factors interleukin-6 (IL-6), interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) play an important regulatory role in the developmental process of cancer pain. IKKβ is a key molecule of the IκB (IKK) kinase that propagates cellular responses to inflammation. Previous studies have shown that phosphorylation and degradation of the IκBα protein promotes the activation of NF-κB and the expression of TNF-α, IL-1β and IL-6, participating in the formation and development of cancer pain. Chanling Gao (CLG) is a compound preparation of traditional Chinese medicine. It contains specific functions, namely nourishing Yin, activating blood circulation and relieving pain and dysfunction syndrome. It is used in the treatment of a variety of pain disorders including cancer-induced bone pain (CIBP), which has a certain relief effect. However, its mechanism of action still remains unclear. In the present study, a rat model of tibia CIBP was successfully established using the Walker 256 breast cancer cell line. The IKKβ/NF-κB signaling pathway and its related factors TNF-α, IL-1β and IL-6 were used as the entry points to explore the effect of CLG on CIBP and their possible mechanisms of action. The results indicated that CLG improved the body mass of the CIBP rat model and increased the pain threshold in rats. CLG significantly inhibited the degradation of IκBα and the levels of p-IκBα, p-IKKβ and p-p65 NF-κB proteins in the spinal cord of CIBP rats, inhibiting the contents of TNF-α, IL-1β and IL-6. Therefore, we conclude that the analgesic effect of CLG in this rat model of CIBP may be related to the inhibition of the IKKβ/NF-κB signaling pathway and the reduction of synthesis and release of TNF-α, IL-1β and IL-6.